PENGARUH PROFITABILITAS, PERTUMBUHAN PENJUALAN DAN KESEMPATAN INVESTASI TERHADAP KEBIJAKAN DIVIDEN (Studi Kasus Pada Perusahaan Manufaktur Selama Tahun 2013â2015) - Aulia Muqsita Majid, 08.3503.0702; Hardiningsih, Pancawati (Students Journal of Accounting and Banking, 2017)
This study examined the effect on profitability, sales growth and the ratio of the market price (MTBV) the dividend policy. Research on this dividend policy using manufacturing companies listed in Indonesia Stock Exchange from the year 2013-2015. Sampel used in this study for three years in a row is 99 companies. This study uses multiple analysis techniques. Based on the results showed that the positive effect on kebijakandividen profitability, sales growth does not affect the dividend policy, the ratio of market price (MTBV) positive effect on dividend policy.Keywords:Â Profitability, Sales Growth (Growth) and The Market Price Ratio (MTBV), The Dividend Policy